Bacterial etiology in acute hospitalized chronic obstructive pulmonary disease exacerbations - Gorek Dilektasli, Asli; Demirdogen Cetinoglu, Ezgi; Ozturk, Nilufer Aylin Acet; Coskun, Funda; Ozkaya, Guven; Ursavas, Ahmet; Ozakin, Cuneyt; Karadag, Mehmet; Uzaslan, Esra (The European Research Journal, 2016)
Introduction. The most common cause of acute COPD exacerbation (AECOPD) is the respiratory tract infections. We sought to determine the bacteriological etiology of hospitalized acute exacerbations of COPD requiring hospitalization in consecutive two years. Methods. We aimed to determine the bacteriological etiology underlying in patients whom admitted to Uludag University Faculty of Medicine, Department of Pulmonary Medicine and hospitalized with AECOPD in the last two years. Medical records of the study participants were screened retrospectively and sociodemographic characteristics, routine laboratory tests and sputum culture results were analyzed. Results. A total of 242 patients hospitalized for AECOPD were enrolled. Of these 86.4% (n=209) were male. The mean age of the group was 66.6±11 years old. Sputum cultures were available in the 45 % (n=109) of the study group. The most frequent bacteria isolated from the sputum cultures of the study group were Pseudomonas aeruginosa, Streptococcus pneumonia, Haemophilus influenzae and Acinetobacter baumanii. Length of stay was longer in patients with the A. baumanii isolate than the rest of the group (p=0.024). Length of stay in hospital was independently associated with in-hospital mortality (OR: 1.37, 95% CI: 1.05–1.78). Isolation of A. baumanii and/or Staphylococcus aureus in sputum culture were identified as independent risk factors for prolonged length of stay in-hospital (b=0.26, p=0.008; b=15.40, p=0.003). Conclusion. Our study shows that P. aeruginosa, S. pneumonia, H. influenzae are common sputum isolates in AECOPD patients requiring hospitalization. Isolation of A. baumanii and/or S. aureus in sputum culture is associated with prolonged length of stay in hospital, which is an independent risk factor for in-hospital mortality.